Insight-HXMT observations on thermonuclear X-ray bursts from 4U 1608–52 in 2022: The accretion rate dependent anisotropy of burst emission - Chen, Yu-Peng; Zhang, Shu; Ji, Long; Zhang, Shuang-Nan; Wang, Peng-Ju; Kong, Ling-Da; Chang, Zhi; Peng, Jing-Qiang; Shui, Qing-Cang; Li, Jian; Tao, Lian; Ge, Ming-Yu; et al. (Journal of high energy astrophysics, 2023)
Thermonuclear X-ray bursts occur on the surface of an accreting neutron star (NS), and their characteristics and interplay with the surrounding circumstance could be a clue to understand the nature of the NS and accretion process. For this purpose, Insight-HXMT has performed high cadence observations on the bright thermonuclear X-ray burster–4U 1608–52 during its outburst in July and August 2022; nine bursts were detected, including seven bursts with the photospheric radius expansion (PRE). Time-resolved spectroscopy of the bright PRE bursts reveals that an enhancement of accretion rate or the Comptonization of the burst emission by the corona could reduce the residuals when fitting their spectra with the conventional model–blackbody. The inferred energy increment rate of the burst photon gained from the corona is up to ∼40%, even though the bursts have different peak fluxes and locate at different accretion rates. Moreover, the flux shortage of the rising PRE is observed in the bursts at a high mass accretion rate, but not for the burst with a faint persistent emission, which has been predicted theoretically but first observed in this work. If the flux shortage is due to the disk obscuration, i.e., the burst emission is anisotropic, the phenomenon above could indicate that the anisotropy of the burst emission is accretion rate dependent, which could also be evidence of the truncated disk in the low/hard state.